TWEAK is not elevated in patients with newly diagnosed inflammatory bowel disease. (3rd April 2017) - Grimstad, Tore; Skoie, Inger Marie; Doerner, Jessica; Isaksen, Kjetil; Karlsen, Lars; Aabakken, Lars; Omdal, Roald; Putterman, Chaim
Abstract: Objective: Tumor necrosis factor-like weak inducer of apoptosis (TWEAK) may be involved in the pathogenesis of inflammatory bowel disease. The aim was to investigate if TWEAK may reflect disease activity in inflammatory bowel disease. Materials and methods: In this cohort study, 139 consecutive patients with newly diagnosed and previously untreated inflammatory bowel disease – 95 with ulcerative colitis (UC) and 44 with Crohn's disease (CD) – underwent colonoscopy. Disease activity was assessed by the Mayo score and the Mayo endoscopic score (MES) for UC, or the Simple Endoscopic Score (SES) for CD. Serum C-reactive protein (CRP) and fecal calprotectin were measured in IBD patients, as were plasma TWEAK levels in patients and 85 healthy subjects. Associations between TWEAK levels and disease activity markers were explored. Results: In the total IBD group, the median (interquartile range) TWEAK level was 430 pg/ml (109–6570), in UC 502 pg/ml (109–4547) and in CD patients 352 pg/ml (101–9179), respectively. Healthy subjects had a median (IQR) TWEAK of 307 pg/ml (63–3492). There were no significant differences in TWEAK levels between the total IBD group and healthy control subjects, nor between UC and CD, or between UC/CD and healthy subjects. Furthermore, we found no significant associations between Mayo scores, MES-UC, SES-CD, CRP, and fecal calprotectin with plasma TWEAK levels. Conclusions: Plasma TWEAK levels do not reflect disease activity or the grade of inflammation in patients with newly diagnosed inflammatory bowel disease. NCT01551563.